Blau syndrome: a case report from Palestine - Salam Iriqat; Mohammed Abu Safieh; Manuel Fatouleh; Abdulsalam Alkaiyat (BMC, 2021)
Abstract Background This case study documents the first familial case of Blau syndrome (BS) in Palestine characterized with mutation in CARD15/NOD2. Case presentation Eighteen years old female was initially misdiagnosed with Juvenile idiopathic arthritis (JIA). The patient had been on steroids and methotrexate treatment for the last 16 years, but did not respond well to treatment. Initial examination at Saint John of Jerusalem Eye Hospital Group clinic showed bilateral intermediate uveitis with camptodactyly. The patient's sister (aged 19 years) had bilateral intermediate uveitis and camptodactyly. Both eyes of their father had signs of old posterior uveitis. Father's left eye showed 360 degrees posterior synechia, mature cataract with old Keratic precipitates (KPs). He also had camptodactyly. The patient was referred to pediatric rheumatologist to rule out sarcoidosis. Lung CT scan showed bronchiectasis, genetic consultation followed. Complete eye examination, full history, refraction, and Optical coherence tomography (oct) were done. Systemic and topical steroid therapy could not control the ocular inflammation. The family then was referred to a geneticist. Genetic analyses showed that the proband and all three family members had an R334q mutation in the CARD15/Nod2 gene. Conclusions BS should be considered in the differential diagnosis of childhood uveitis, especially in low and middle income countries where it is misdiagnosed in many cases, which delay appropriate diagnosis and thus control. Genetic analysis of the CARD15/Nod2 gene is helpful in the diagnosis. Steroids alone are not enough to control the disease, other immunosuppressants and biologics are needed.